Metodologie, percorsi operativi e strumenti per lo sviluppo delle cooperative di comunità nelle aree interne italiane - Mastronardi, Luigi; Romagnoli, Luca (Studi e saggi, 2020)
The present essay includes the main results of the research project on community-based cooperatives, promoted in 2018 by Fondosviluppo and FEDAM, and implemented by researchers of University of Molise. The volume highlights the potential and the modes of operating of community-based cooperatives, which carry out a mix of productive and socially useful activities for local community well-being. The research, through a new methodological and operational path, reaches the following results: a) devise a strategy to detect the degree of social, economic and environmental vulnerability levels of Italian inner areas; b) outline the needs of local communities; c) define the role of community-based cooperatives in bridging regional gaps, also identifying their possible policy support.